Strategi Komunikasi Antarbudaya dalam Mengelola Stereotip dan Perbedaan Nilai pada Pernikahan Beda Agama: (Studi Kasus Kabupaten Nganjuk) - Febrin Nungki Kusumaning Astri; Nikmah Suryandari (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this study is to examine how married couples from different religions can maintain the harmony of their households, especially in the Nganjuk Regency area. Married couples of different religions often face various obstacles, such as negative judgments from the surrounding community, differences in life values, and pressure from extended families. Using a qualitative method with a phenomenological approach, this study involved three couples who underwent interfaith marriages. The results showed that despite the challenges of social stereotypes and differences of opinion, they were able to maintain good relationships through honest communication, mutual respect, and mutual commitment. In addition, they also try to understand each other's beliefs and form a balanced agreement in daily life. This study concludes that interfaith marriages can still run happily as long as both couples have an open attitude towards each other, are willing to respect differences, and continue to learn together.